Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1982
DOI: 10.1143/jjap.21.l381
|View full text |Cite
|
Sign up to set email alerts
|

Velocity-Modulation Transistor (VMT) –A New Field-Effect Transistor Concept

Abstract: Unit-cell parameters for the stoichiometric composition BizSeTez have been determined accurately, using the least-square method, for reflections in the range of Bragg angles of 62-85 ' . A study of the thermal expansion of the layer-structure unit cell, determined over the temperature range 30-525 "C, has revealed the anisotropy between the axial expansion coefficients, that for the c axis ( 1 6 . 2~ 10-6OC-1) being about 15 times that for the a axis (10.2 x 10-6°C-1) at 50°C. The anisotropy almost disappears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
4

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(41 citation statements)
references
References 6 publications
0
37
0
4
Order By: Relevance
“…Despite the susceptibility of black phosphorus to photo-oxidation [4], improvements to the electronic quality of black phosphorus devices has culminated in the observation of the quantum Hall effect [5]. In this work, we demonstrate the room temperature operation of a dual gated black phosphorus transistor operating as a velocity modulated transistor [6], whereby modification of hole density distribution within a black phosphorus quantum well leads to a two-fold modulation of hole mobility. Simultaneous modulation of Schottky barrier resistance leads to a four-fold modulation of transconductance at a fixed hole density.…”
mentioning
confidence: 92%
“…Despite the susceptibility of black phosphorus to photo-oxidation [4], improvements to the electronic quality of black phosphorus devices has culminated in the observation of the quantum Hall effect [5]. In this work, we demonstrate the room temperature operation of a dual gated black phosphorus transistor operating as a velocity modulated transistor [6], whereby modification of hole density distribution within a black phosphorus quantum well leads to a two-fold modulation of hole mobility. Simultaneous modulation of Schottky barrier resistance leads to a four-fold modulation of transconductance at a fixed hole density.…”
mentioning
confidence: 92%
“…MC profiles of electron concentration and mean velocity in both high-µ and low-µ channels for different biasings demonstrate the velocity-modulation operation of the proposed transistor [7,8]. Concerning the dynamic performance of the 100 nm gate device, MC results show that the cut-off frequencies take values much lower than predicted [9] (the maximum value of f C estimated with the MC model is of the order of 200 GHz for a geometry similar to that of the experimental device [8]) because of the low g m associated to the VM behavior and, remarkably, to the high geometrical capacitance existing between the two gate electrodes when operating in DM, which is the main contribution to C IN [7,8]. To improve the frequency operation, the VMT geometry must be optimized for an enhanced g m and reduced C IN .…”
Section: Physical Modelmentioning
confidence: 75%
“…Thus, the drain current I D is modulated while keeping constant the total carrier density, and it is in principle possible to overcome the transit--time limit for high-frequency applications. However, the dynamic behavior of the VMT is not as exceptional as expected [9] due to the low values of the transconductance g m , and mainly due to the high capacitance be- * corresponding author; e-mail: bgvasallo@usal.es tween both gates C g1g2 [8]. In contrast, this device does not follow the traditional scaling rules for standard field effect transistors (FETs) and provides a high immunity to short-channel effects [8].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We found that the band gap of the heterostructures was extended obviously. Heterostructure engineering is now widely practiced, producing the most efficient semiconductor lasers [9], highest-speed transistors [10], and novel quantum electronic devices [11]. If the nontransmission frequency range (PBG along the incident direction) of the constituents has a proper lineup, this can be essentially enlarged as desired by using different PCs to form photonic multiple heterostructures.…”
Section: Introductionmentioning
confidence: 99%